Identifikasi Potensi Pakan dan Telur Cacing Parasit pada Ular Hijau Ekor Merah (Trimeresurus insularis), di Taman Wisata Alam Bipolo Kabupaten Kupang - Brilian Santoso Ndun; Herlina Umbu Data; Yeremia Y Sitompul; Yohanes T.R.M.R Simarmata (Jurnal Veteriner Nusantara, 2023)
White-lipped Green Pitviper (Trimeresurus insularis) in the Bipolo Nature Park has a green body with red color at the tip of the tail and a heat pit that is used in hunting prey at night. This study aims to identify the food potential of Trimeresurus insularis in the Bipolo Nature Park and identify parasitic worm eggs in Trimeresurus insularis through simple flotation method feces examination using saturated sugar solution as a floating solution. The results showed that the main food potential of Trimeresurus insularis in the Bipolo Nature Park area is the type of amphibian Frogs Tegalan (Fejervarya limnocharis). The results of fecal examination showed that Trimeresurus insularis was infected with parasitic worms from the nematelminthes phylum of the nematode class: Ascaridia sp, Nematodirus sp and Oxyuris sp.